Lipoprotein Lipase Gene PvuII Polymorphism Serum Lipids and Risk for Coronary Artery Disease: Meta-Analysis - Cagatay, Penbe (IOS Press, 2007)
Our aim was to determine whether lipoprotein lipase gene PvuII polymorphism can be considered as an independent risk factor for coronary artery disease (CAD) by conducting a meta-analysis of all available published trials, including our own study. In 7 seperate studies, 3289 subjects were screened for this substitution; meta-analysis included only some of these individuals. Among the 7 studies, 6 were performed on white subjects, whereas 1 was on patients with Saudi Arabic descent.Subgroup analysis indicated that individuals with PvuII substitution does not have an increased risk for CAD. The LPL-PvuII genotype and allele frequency distributions did not differ significantly between CAD patients and healthy controls. There was no difference in the distribution of LPL-PvuII genotypes between the healthy subjects and the patients with CAD. However, no significant differences in lipid variables (triglyceride and HDL-cholesterol) were determined for the PvuII polymorphisms in the patients with CAD. No significant differences were found in serum triglyceride and HDL-cholesterol levels for LPL-PvuII genotypes when the control and CAD groups were pooled. In conclusion, LPL-Pvu II polymorphism cannot be used as independent genetic risk factor for CAD.